7f-1=45

Simple and best practice solution for 7f-1=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7f-1=45 equation:


Simplifying
7f + -1 = 45

Reorder the terms:
-1 + 7f = 45

Solving
-1 + 7f = 45

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 7f = 45 + 1

Combine like terms: -1 + 1 = 0
0 + 7f = 45 + 1
7f = 45 + 1

Combine like terms: 45 + 1 = 46
7f = 46

Divide each side by '7'.
f = 6.571428571

Simplifying
f = 6.571428571

See similar equations:

| (y+5/3)-3=6 | | 5e-6-4=-3 | | x(2x-2)+x(3x-4)=(5x+6)(x-4) | | -126=14*k | | 6z+5(z-6)= | | (5e-6)-4=-3 | | 4x-1-4x+7= | | 4x+x=-27 | | 21=-7*n | | -13=-8b-5b | | -6x-50+12x=64 | | 4x-4=27 | | 0.15x+0.6(x-2)=0.01(3x-5) | | 5(-5)-2(2)= | | 11t/28-t/4=1 | | x-2(3x-2)=-6+4x-8 | | -15*x=2 | | g(-x)=x^2+10x+35 | | 5-4(3m-6)=5 | | 4(3+1.25)+5y=12.00 | | 6y+3-8=-37 | | 5x+6x-(3x+5)= | | V+9=1 | | x^3-6x+9x=0 | | 6n+4+2=-24 | | -10-5(1+j)= | | -2x+1=-2(x+5) | | 6x-8+8=6 | | 3(-9h+10)= | | 13/1/3 | | 3(x^2-1)=24 | | 5(-7g-2)= |

Equations solver categories